2016
DOI: 10.1080/03650340.2016.1193163
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions in response to straw incorporation, water management and their interaction in a paddy field in subtropical central China

Abstract: A field experiment was conducted to study the effects of combination of straw incorporation and water management on fluxes of CH 4 , N 2 O and soil heterotrophic respiration (Rh) in a paddy field in subtropical central China, by using a static opaque chamber/gas chromatography method. Four treatments were set up: two rice straw incorporation rates at 0 (S1) and 6 (S2) t ha -1 combined with two water managements of intermittent irrigation (W1, with midseason drainage) and continuous flooding (W2, without midsea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Wang et al. (2017) also reported that approximately 69% of rice straw in China was burned due to limited time to prepare for the next crop. Chinese scientists have invented a new mechanical transplanting technique that can deliver fertilizer to a depth of 10 cm (Li et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al. (2017) also reported that approximately 69% of rice straw in China was burned due to limited time to prepare for the next crop. Chinese scientists have invented a new mechanical transplanting technique that can deliver fertilizer to a depth of 10 cm (Li et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Global warming, resulting from significantly increased greenhouse gas (GHG) emissions since the Industrial Revolution, has become a major global problem [1] (Wang et al, 2017). The Intergovernmental Panel on Climate Change [2] (IPCC 2022) has estimated that the Earth's surface will warm by 1.5-1.6 • C by approximately 2040.…”
Section: Introductionmentioning
confidence: 99%
“…(3) What are the economic, environmental, and comprehensive benefits for garlic fields of using polyethylene and biodegradable films? The objectives of this study are as follows: (1) to compare the effects of different film covers (none, plastic, and biodegradable plastic) on GHG (CH 4 and N 2 O) emissions and garlic yields; (2) to assess the impacts of the different film covers on the carbon footprint and economic outputs of garlic production; and (3) to determine the optimal film cover method for garlic fields with regards to maximizing the film cover effect and maintaining crop yields. This research clarifies carbon sequestration and provides technical support for achieving the green and low-carbon development of the garlic industry.…”
Section: Introductionmentioning
confidence: 99%